QUANTIFICATION OF TRACTION TO DELIVER THE BUFFALO CALF DURING FORCED CALVING AND ITS INFLUENCE ON BLOOD GAS AND ACID-BASE PARAMETERS - PRABHAKAR, S; PRABHAKAR, S; SINGH, A K; BRAR, P S; SINGH, TARUNBIR (The Indian Journal of Animal Reproduction, 2023)
Calculation and measurement of manual traction was recorded during 21 extractions in buffalo dystociascategorized under mild assistance (Mi A}, moderate assistance (Mo A) and forced assistance (Fo A) groups (n =7; each). The blood samples were taken from the jugular venipuncture and the acid-base status of buffalo calvesdelivered through manipulation and forced extraction was studied over a period of five hours immediately aftercalving. The influence of the number of pulls, maximum force ·of traction and relative force of traction upon the perinatalblood gas and acid-base values, and the vitality of the calves were investigated. It appeared that calvesdelivered with minimum, moderate and forced assistance exhibited a descending trend in parity (5.9 ± 0.3, 3.6 ±0.2 and 1.3 ± 0.2, respectively). The time taken to deliver the fetus was significantly (P < 0.05) less in Mi A (4.1 ±1.3 minutes) than in MoA(7.9 ± 1.1 minutes) and FoA(12.3 ± 1.4 minutes) groups. This was positively correlatedwith the number of pulls and number of assistants involved in pulling, thereby signifying the impact of parity on theabove-mentioned parameters. Similarly, both maximum force of traction and relative force of traction were significantly(P < 0.05) lesser in Mi A group (1323.8 ± 6.2 Newton and 42.3 ± 2.2 Newton) as compared to their counterparts(2752.5 ± 7.3 Newton and 84.6 ± 3.5 Newton in Mo A; 4246.8 ± 9.1 Newton and 127.9 ± 5.1 Newton in FoA). Asignificant (P < 0.05) decreasing trend was also observed at the level of internal pelvic area (380.9 ± 10.9 cm2 vs298.2 ± 12.3cm2 vs216.4 ± 9.2 cm2) and external pelvic area (652.1± 14.7 cm2 vs 558.3 ± 12.1 cm2 vs497.6 ± 10.5cm2) in the Mi A, Mo A and Fo A groups, respectively. The calves delivered by means of minimum assistanceshowed substantial, metabolic acidosis for about 1 h. Metabolic acidosis was severe in the calves which weredelivered by moderate and forced extractions that persisted for nearly 2-3 h. Any change in the acid-base statusof the calf during extraction was evidently correlated with the number of pulls, time to deliver the fetus and the forceof traction. It is shown that in complicated cases, the traction needs to be interrupted repeatedly, to give the calfthe opportunity to breathe.
Keywords: Acid-base profile; Buffalo; Calving; Traction